"One that has given you little has your soul consoled” – unemployed youth on surviving without unemployment benefi ts in Namibia (Journal for Studies in Humanities and Social Sciences, 2016)
Alarmingly, youth unemployment rates in Namibia are among the highest in Southern Africa. This fact haunts Namibia terribly. The unemployment of those that should be the main bread winners does not only affect them as individuals, but also bears a negative impact on their families and friends. With poor access to productive assets such as capital, land and skills, the majority of the unemployed youth face a daily struggle to meet their basic needs and are often the ones on the periphery of the Namibian society. The difficulties in finding employment also mean difficulties in securing an income and a decent livelihood for these young people. In absence of a social protection system for unemployed people in Namibia, the situation of the youth is exacerbated. This study seeks to understand the social support system and survival strategies of the unemployed youth in Namibia. It draws data from the author’s on-going PhD research for which she conducted interviews with unemployed youth from Ohangwena and Khomas regions, with the aim to capture the lived experiences as well as the views of young people on the problem of youth unemployment in Namibia. The results point to the practical difficulties of unemployment the youth experience in their everyday lives. Findings indicate that the majority of youth are the most likely to fill low-quality jobs in the menial and informal economy rather than jobs with decent wages and benefits. In as much as the youth are engaging in the informal employment and economy, they do not regard it as employment. Consequently, many rely on family and friends for support in order to survive unemployment. As an onset to assist the unemployed, the author therefore propose the Basic Income Grand (BIG) as one way of socio-economic safety of the poor and unemployed as they persevere with their unemployment. Such an initiative can ameliorate the negative effects of unemployment specifically among the youth. This however, should not be regarded as a replacement for the possibility of unemployment benefit.